LEADER IS A MENTOR OR BOSS - A REVIEW DISCUSSION IN LEADERSHIP PSYCHOSOCIAL REHABILITATION - Narayanan, Raja; Sharma, Sandhir (International Journal of Psychosocial Rehabilitation, 2020)
In any research, review is the key to further enquiry. This article presents reviews of leadership among teaching community. The reviews are presented in a logical order based on the topics and publication, clustered in the chronological order under appropriate headings. Its started with origin, and a glance of world leaders followed by religion leaders and leaders and their styles. This article is fully review based discussion and spoke about different elements of leaders like, Lessening, Empathy, Healing, Persuasion, Awareness, Foresight and Conceptualising.